Strength abilities: pattern recognition method in the management of the cumulative effect of strength loads in 8-year-old boys - Olha Ivashchenko; Oleg Khudolii; Wladyslaw Jagiello (IP Iermakov S.S., 2021)
Background and Study Aim. The purpose of the study was to determine the peculiarities of using pattern recognition method in the management of the cumulative effect of strength loads in 8-year-old boys. Materials and methods. The study participants were 48 boys aged 8. The experiment was conducted using a 22 factorial design. The study materials were processed by the IBM SPSS 22 statistical analysis program. Discriminant analysis was performed. The study examined the impact of four variants of strength load on the formation of the cumulative training effect of three, six, nine, and twelve classes in 8-year-old boys. Results. The discriminant analysis provided information about the impact of four orthogonal variants of strength loads on the formation of the cumulative training effect of strength exercises of three, six, nine, and twelve classes in 8-year-old boys. The obtained data make it possible to choose a load mode at each step of the CTE formation and to manage schoolchildren's strength training. Conclusions. The verification of the obtained discriminant functions shows their high discriminative ability and value in interpretation with respect to the general population (p < 0.05). It was found that the formation of the CTE of three classes is most influenced by the third load variant, six classes - by the third load variant, nine classes - the third load variant, twelve classes - the first load variant. The discriminant function structure coefficients made it possible to identify the factor structure of the CTE of 3, 6, 9, 12 classes, to find that the CTE3, CTE6 are associated with the work at the first place "Exercises to strengthen arm muscles", the CTE9, CTE12 - with the work at the third ("Exercises to strengthen back muscles") and the fourth ("Exercises to strengthen leg muscles") places. The CTE of three, six, nine, and twelve classes depends on the modes of strength exercises and has different focuses. The CTE3 - speed and strength focus; CTE6, 9 - comprehensive focus; CTE12 - explosive-strength focus. The obtained values of centroids for the CTE of 3, 6, 9, 12 classes enable the management of schoolchildren's strength training.